(x2+3x-6)=(x+4)

Simple and best practice solution for (x2+3x-6)=(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x2+3x-6)=(x+4) equation:



(x2+3x-6)=(x+4)
We move all terms to the left:
(x2+3x-6)-((x+4))=0
We add all the numbers together, and all the variables
(+x^2+3x-6)-((x+4))=0
We get rid of parentheses
x^2+3x-((x+4))-6=0
We calculate terms in parentheses: -((x+4)), so:
(x+4)
We get rid of parentheses
x+4
Back to the equation:
-(x+4)
We get rid of parentheses
x^2+3x-x-4-6=0
We add all the numbers together, and all the variables
x^2+2x-10=0
a = 1; b = 2; c = -10;
Δ = b2-4ac
Δ = 22-4·1·(-10)
Δ = 44
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{44}=\sqrt{4*11}=\sqrt{4}*\sqrt{11}=2\sqrt{11}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-2\sqrt{11}}{2*1}=\frac{-2-2\sqrt{11}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+2\sqrt{11}}{2*1}=\frac{-2+2\sqrt{11}}{2} $

See similar equations:

| X+.09x=2000 | | 15w-11w=20 | | -3=7p-5-5 | | 11x-42=5x-6 | | (8+y)*y=60 | | x^2(x+2)(x+2)=100 | | 18r-17r=1 | | 5-1x=11 | | -7x+13+9x+21=-2 | | 52=277-w | | 10−3y=4 | | 4+(x+5/8)=20 | | 92/x=-7=16 | | 3x-0,8=2,4x+1,6 | | 1/9^4x=27 | | 4z/7+6=-8 | | 62*8/x+41=55 | | x+5x+4x-8=180 | | -x+196=89 | | X+11+2x-5=180 | | 3x8+x=28 | | 15=50m | | 5/4x+3=5/6x+4 | | 5q+5q=20 | | 227=-y+3 | | 80+64t-16^2=0 | | z/8+6=9 | | 7x-4=-109 | | 21b=24 | | 6/7d=42 | | 6.49s=19.46 | | 13x+9=11x-5. |

Equations solver categories